Measures on coallocation and normal lattices - Jack-Kang Chan (International Journal of Mathematics and Mathematical Sciences)
Let ℒ1 and ℒ2 be lattices of subsets of a nonempty set X. Suppose ℒ2 coallocates ℒ1 and ℒ1 is a subset of ℒ2. We show that any ℒ1-regular finitely additive measure on the algebra generated by ℒ1 can be uniquely extended to an ℒ2-regular measure on the algebra generated by ℒ2. The case when ℒ1 is not necessary contained in ℒ2, as well as the measure enlargement problem are considered. Furthermore, some discussions on normal lattices and separation of lattices are also given.